Approximation of electro-optical hysteresis characteristics of ChLC - Rybalochka, A.; Chumachkova, M.; Sorokin, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In order to select proper cholesteric liquid crystal (ChLC) materials and drive schemes for cholesteric liquid crystal displays (ChLCD), it is necessary to make the protracted experimental analysis of electro-optical hysteresis properties of ChLCs. Method for approximation of electro-optical characteristics of ChLC offered in this article significantly decreases duration of experimental analysis above. Accuracy of this method is estimated by the comparison of volt-brightness and volt-contrast characteristics of ChLC obtained both by experimental measuring and proposed method of approximation.